Evaluation of the tryptophan requirement of small-framed first cycle laying hens. (15th October 2018) - Wen, J; Helmbrecht, A; Elliot, M A; Thomson, J; Persia, M E
ABSTRACT: An experiment was conducted to evaluate the total Trp requirement of first cycle laying hens from 41 to 60 wk of age. In total, 270 Hy-Line W36 laying hens were randomly allocated to six treatments with 15 replicate groups of three birds for each experimental unit. A Trp-deficient basal diet was formulated with corn, corn gluten meal, and soybean meal with determined Trp, Lys, and crude protein concentrations of 0.096%, 0.873%, and 15.0%, respectively. Synthetic L-Trp was supplemented to the basal diet in 0.020% increments to generate experimental diets containing 0.096%, 0.116%, 0.136%, 0.156%, 0.176%, and 0.196% Trp, respectively. Hens were provided a controlled amount of feed of approximately 95 g/d. The diet containing the lowest concentration of Trp resulted in reduced egg production and was halted at 45 wk of age due to low performance with all other dietary treatments reaching the conclusion of the experiment at 60 wk of age. Plasma serotonin responded to dietary Trp concentration, but was not a good candidate for Trp requirement estimation. Linear broken line, quadratic broken line, quadratic polynomial, and exponential models were used to estimate Trp requirement based on hen-housed egg production (HHEP), egg mass (EM), and feed conversion ratio (FCR). HHEP ranged from 50.7% to 81.0%, dependent upon dietary concentration of Trp. Tryptophan requirements estimated by linear broken line, quadratic broken line, quadratic polynomial, and exponential models were reported. Using the linear broken line model, Trp requirement was highest for EM, 155.8 mg/d, followed by egg production, 153.2 mg/d and lowest for FCR, 140.4 mg/d.